Modified gradual ulnar lengthening for treatment of Masada type IIb forearm deformity in children with hereditary multiple osteochondromas - Fan, Jingyi; Zhang, Xuejun; Sun, Lin; Li, Chengxin; Qi, Xinyu; Sun, Baosheng (Frontiers in Pediatrics, 2023)
Objective: To investigate the effect of modified gradual ulnar lengthening in the treatment of Masada type IIb forearm deformity in children with hereditary multiple osteochondromas (HMO). Patients and methods: From May 2015 to October 2020, 12 children with Masada type IIb forearm deformity caused by HMO underwent modified gradual ulnar lengthening in our hospital. Clinical and imaging data were retrospectively analyzed. Clinical evaluation included wrist flexion and extension, wrist ulnar and radial deviation, forearm pronation and supination, and elbow range of motion. The radiographic parameters measured included the radial articular angle, carpal slip, and relative ulnar shortening. Results: The mean operative age of the 12 patients (9 male, 3 female) was 8.5±2.7 years, the mean follow-up was 31.5±5.7 months, and the mean ulnar lengthening was 43.3±9.9 mm. There was no significant difference in the radial articular angle between the preoperative period and the last follow-up (from 36.5°±9.2° to 33.8°±5.1°, p>0.05). However, significant changes were found in carpal slip (from 61.3%±18.8% to 33.8%±20.8%) and relative ulnar shortening (from 5.8±3.5 mm to −0.9±4.85 mm) (p<0.05). The range of motion significantly improved after modified gradual ulnar lengthening, including wrist flexion (from 38.3°±6.2° to 55.8°±9.0°), wrist extension (from 45.0°±9.8° to 61.7°±8.1°), wrist ulnar deviation (from 41.3°±8.6° to 29.6°±7.8°), wrist radial deviation (from 18.3°±6.2° to 30.0°±5.6°), forearm pronation (from 44.6°±7.2° to 62.1°±8.6°), forearm supination (from 50.0°±7.1° to 52.9°±6.6°), and elbow range of motion (from 117.1°±10.1° to 127.9°±5.4°) (all p<0.05). During follow-up, there was one case of needle tract infection and one case of bone nonunion. Conclusion: Modified gradual ulnar lengthening can effectively treat Masada type IIb forearm deformity caused by HMO and improve forearm function.